Endoscopic Endonasal Resection of a Suprasellar Pituitary Adenoma Mimicking Tuberculum Sellae Meningioma in a Patient with an Intrasellar Persistent Trigeminal Artery - Montaser, Alaa S.; Todeschini, Alexandre B.; Revuelta Barbero, Juan M.; Shahein, Mostafa; Chiocca, E. Antonio; Otto, Bradley A.; Carrau, Ricardo L.; Prevedello, Daniel M. (Journal of Neurological Surgery Part B: Skull Base, 2018)
A 50-year-old female with an incidentally diagnosed suprasellar lesion was initially managed conservatively due to the presence of an intrasellar persistent trigeminal artery going through the dorsum sellae and fundamentally forming the blood supply of the entire posterior circulation. Serial follow-up brain magnetic resonance imaging (MRI) revealed progressive enlargement of the suprasellar lesion over 4 years period. Surgery was indicated after the initial tumor growth; however, the patient refused surgery for fear of complications related to the persistent trigeminal artery. Two-and-a-half years later, she presented with deterioration of vision. Formal visual field testing revealed a right temporal field defect. Brain MRI demonstrated significantly enlarged suprasellar lesion, most consistent with tuberculum sellae meningioma, exerting mass effect on the optic apparatus.The patient underwent endoscopic endonasal resection of the lesion through a transplanum/transtuberculum approach. Intraoperatively, absence of hypertrophic McConnel arteries, hyperostosis, and the fact that the dura was soft and not under tension was against the diagnosis of tuberculum sellae meningioma. Additionally, the tumor consistency was similar to a pituitary adenoma. A complete resection was accomplished and multilayer skull base reconstruction was performed with no complications. On postoperative day 1 (POD 1), she was operated upon for the evacuation of small suprasellar hematoma associated with vision deterioration. Histopathological examination confirmed the diagnosis of atypical pituitary adenoma with Ki-67 labeling index of 4 to 5%. The patient ultimately recovered well with improved vision, and was discharged on POD 4 with no new neurological deficits. At 4 years follow-up, her vision was normalized and brain MRI showed no residual or recurrent lesion.The link to the video can be found at: https://youtu.be/QZmzctjAEbw.
Keywords: endoscopic endonasal; persistent trigeminal artery; pituitary adenoma; suprasellar